ECOLOGÍA DE LA ANIDACIÓN DE CROCODYLUS ACUTUS (REPTILIA: CROCODYLIDAE) EN LA DESEMBOCADURA DEL RÍO CUITZMALA, JALISCO, MÉXICO - Casas Andreu, Gustavo (Instituto de Ecología, A.C., 2003)
The nesting ecology of the American crocodile (Crocodylus acutus) was studied in the region of the Cuitzmala river mouth in Jalisco State, Mexico, from 1990 to 1993. Nesting occurred from mid-April to May, during the annual dry season, coinciding with high daily temperature variations. The initiation of nesting also appeared to be related to the presence of a new moon. Compared to other sites along the Pacific coast of the Americas, C. acutus in Jalisco nests late in the year, and timing of nesting appears to be related to latitude. Populations of C. acutus along the Gulf of Mexico and Caribbean show a similar latitudinal pattern. Females exhibit a tendency to nest fidelity. Total length of the smallest nesting female was estimated to be 225 cm, and largest was 305 cm. Nests were holes excavated in sand, sand-lime, or sand-lime-clay soils and percent of soil moisture ranged from 0.48% to 25.58%, with pH close to neutrality. Nests in sandy soils tended to have lower soil moisture levels and higher temperatures. Most nests faced south, and vegetation cover ranged from 0% to 30%. Clutch size ranged from nine to 54 (mean 27.9 ± 13.2). Overall egg viability was 80.7 ± 21.0%. It was found that larger females tend to have larger and heavier eggs, higher egg viability and natality. Hatching takes place during the annual rainy season.